Transcriptional regulation, nucleotide sequence, and localization of the promoter of the catBC operon in Pseudomonas putida. - Aldrich, T L (1988)
The catB and catC genes encode cis,cis-muconate lactonizing enzyme I (EC 5.5.1.1) and muconolactone isomerase (EC 5.3.3.4), respectively. These enzymes are required for the dissimilation of benzoate to beta-ketoadipate by Pseudomonas putida and are under coordinate transcriptional regulation. By deletion analysis and the use of pKT240 as a promoter probe vector, we located a single promoter region for the catBC operon upstream of catB. RNA-DNA hybridization studies, together with reverse transcriptase mapping, demonstrated that this promoter must be activated in the presence of an inducer molecule for effective transcription of the operon. In addition, the transcription initiation site was located 64 base pairs upstream of the catB initiation codon, and sequences upstream of -43 were required for promoter function. The catBC promoter was compared with other positively regulated procaryotic promoters to identify possible consensus sequences.